EMBODIED LEARNING: CONNECTING PSYCHOLOGY, EDUCATION, AND THE WORLD - Thea IONESCU; Adina GLAVA (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia, 2015)
This opinion article is aimed to bridge new approaches in psychology with the efforts to change schools that are widely advocated in educational sciences. To reach this aim we review the embodied cognition approach and the problems that schools face today, and then we argue for the role that embodied learning might play in the process of changing education as it is pursued today. We conclude with ideas on the importance of putting the learner back in the world when he/she learns in order to be able to better adapt to the world.